Introduction to the Special Issue "Migrant Youth, Intercultural Relations and the Challenges of Social Inclusion" - Mansouri, Fethi (Social Inclusion, 2014)
This Special Issue on “Migrant Youth, Intercultural Relations and the Challenges of Social Inclusion”, reports recent cutting edge research into the complex nature of migrant youth settlement in multicultural émigré societies. Drawing on multidisciplinary research, it explores the latest intersecting theories on cultural diversity, intercultural relations and multiculturalism in the context of globalised cities where access to and sharing of public spaces is becoming a highly contested issue.